Exposure of male mice to perfluorooctanoic acid induces anxiety-like behaviors by increasing corticotropin-releasing factor in the basolateral amygdala complex. (January 2022) - Wang, Ya; Zhang, Yajie; Shi, Zhaochun; Di, Tingting; Yu, Wenfeng; Chen, Ling
Abstract: Perfluorooctanoic acid (PFOA), a hazardous environmental pollutant, has been found to enhance hepatic synthesis of fibroblast growth factor 21 (FGF21). FGF21 can enter the brain and increase the expression of corticotropin-releasing factor (CRF) in the paraventricular nucleus (PVN). In this study, adult male mice were orally administered PFOA to evaluate how it regulates emotion. Exposure of mice to PFOA (1 mg kg-1 bw) for 10 consecutive days (PFOA-mice) caused anxiety-like behaviors and a peroxisome proliferator-activated receptor α (PPARα)-dependent increase in hepatic FGF21 synthesis. The levels of CRF expression in not only PVN but also basolateral amygdala complex (BLA) neurons of PFOA-mice were increased via FGF receptor 1 (FGF-R1) activation. However, the microinjection of FGF-R1 or CRF 1 receptor (CRF-R1) antagonist in the BLA rather than the PVN of PFOA-mice could relieve their anxiety-like behaviors. In addition, external capsule-BLA synaptic transmission in PFOA-mice was enhanced by increasing CRF-R1-mediated presynaptic glutamate release, which was corrected by the blockade of PPARα, FGF-R1 and CRF-R1 or the inhibition of PKA. Furthermore, the threshold of frequency-dependent long-term potentiation (LTP) induction was decreased in the BLA of PFOA-mice, which depended on the activation of PPARα, FGF-R1, CRF-R1, PKA and NMDA receptor (NMDAR), whereas long-term depression (LTD) induction was unchanged. Thus, the results indicate that the exposure of male mice to PFOA (1 mg kg-1 bw) enhances CRF expression in BLA neurons by increasing hepatic FGF21 synthesis, which then enhances CRF-R1-mediated presynaptic glutamate release to facilitate NMDAR-dependent BLA-LTP induction, leading to the production of anxiety-like behaviors. Highlights: Exposure of mice to PFOA increases hepatic FGF21 synthesis via PPARα activation. Increased PPARα-FGF21 in PFOA-mice enhances CRF expression in BLA neurons. BLA-CRF enhances CRF 1 receptor-mediated presynaptic glutamate release. High activation of BLA synapses facilitates NMDA receptor-dependent LTP induction. Enhancement of BLA-LTP induction leads to production of anxiety-like behaviors.